If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3.2 = 0 Reorder the terms: 3.2 + 2x = 0 Solving 3.2 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.2' to each side of the equation. 3.2 + -3.2 + 2x = 0 + -3.2 Combine like terms: 3.2 + -3.2 = 0.0 0.0 + 2x = 0 + -3.2 2x = 0 + -3.2 Combine like terms: 0 + -3.2 = -3.2 2x = -3.2 Divide each side by '2'. x = -1.6 Simplifying x = -1.6
| y(y+14)=48 | | -6(t-8)-(t+6)=7 | | 7p+4=2p+19 | | 4x*2-4=0 | | 2(x+2)=3(x-4) | | 7x-25=10 | | 1=15y-x | | 121-7x=9x+23 | | 140-5x=4x+23 | | 3f-2=-14 | | 6y=3y-4 | | 2x-5=6x+25 | | 5(6z-1)-3(z+2)=10(z+1) | | 6r-3=2 | | 5x^2-42x+88=0 | | 8-27x^3=0 | | 14-7x+2x=-10x+39 | | -12x+1=-15x-20 | | 2*-2+9*7-5= | | 99+99= | | x-x^2=1-6x^2 | | 6(3z-1)-3(z+7)=4(z+1) | | (2z+1)(2z-1)=-4z^2-5z+2 | | x^2+.8x-1=0 | | B^2+4b-60= | | 3y^2+24y-60= | | 3x^2y-5xy^2= | | (x-1)=(0.5x+1) | | y^3-y^2-y= | | 6a+4b+c=40 | | (x-1)(0.5x+1)= | | 2x^3+4x^2+6x= |